Relations among age, simple information processing speed, complex information processing speed, memory, and set-shifting - Jurkuvėnas, Vytautas (Psichologija, 2015)
Age is related to the decline in processing speed and other fluid cognitive performance (like memory or set-shifting) in adult population. T. A. Salthouse’s (1996) theory of adult age differences in cognition postulates that age changes in processing speed are the leading indicator of cognitive aging. However, the construct of information processing speed can be conceptualized and measured as two distinct cognitive functions: simple and complex information processing speed (Chiaravalloti, Christodoulou, Demaree, & DeLuca, 2003). The aim of this study was to explore direct and mediating relations among age, simple information processing speed, complex information processing speed, memory, and set-shifting. In total, 415 adults participated in the study. Participants completed a battery of eleven computer-administered tasks measuring one of the four cognitive functions: simple information processing speed, complex information processing speed, memory, and set-shifting. The confirmatory factor analysis was used to confirm the four-factor structure (X2 = 83,035; df = 47; p = 0,001, RMSEA = 0,043, CFI = 0,973, TLI = 0,961). Also, participants answered additional questions about their family status, occupational status, sex, native language, education, and age. The Pearson correlation coefficients were calculated between age, simple information processing speed, complex information processing speed, memory, and set-shifting. Also, the confirmatory path analysis was used to evaluate direct and mediating relations among these variables. Four models were tested: 1) the saturated model of age, simple information processing speed, memory, and set-shifting; 2) the optimized model of age, simple information processing speed, memory, and set-shifting; 3) the saturated model of age, simple information processing speed, complex information processing speed, memory, and set-shifting; 4) the optimized model of age, simple information processing speed, complex information processing speed, memory, and set-shifting. The results indicate that age is strongly related to the simple information processing speed, the complex information processing speed, and memory. The simple information processing speed mediated the effect of age on memory and partially mediated the effect of age on set-shifting. The simple information processing speed only partially mediated the effect of age on the complex information processing speed. The complex information processing speed mediated the effect of the simple information processing speed on set-shifting and partially mediated the effect of the simple information processing speed on memory.